Physical, Mechanical And Environmental Properties Of Dental Resin Composites Based On Hydroxyapatite Filled BIS-GMA / Tegdma - Alsharif, Saad Omar (2011)
Dental resin composite (white filling) was prepared by incorporating hydroxyapatite (HA) as filler into high viscosity monomer bisphenol A-glycidyl dimethacrylate (Bis-GMA). Bis-GMA monomer was mixed mechanically with a low viscosity monomer triethyleneglycol dimethacrylate (TEGDMA) as diluent monomer, camphorquinone (CQ) was used as initiator and dimethylaminoethyl methacrylate (DMAEMA) was used as accelerator. HA particles were treated with silane coupling agent 3-(Trimethoxysilyl) propyl methacrylate (γ-MPS) before incorporating into Bis-GMA/TEGDMA.